Acceptance and present-moment awareness in psychiatric disorders: Is mindfulness mood dependent?. (March 2019) - Elices, Matilde; Tejedor, Rosa; Pascual, Juan C.; Carmona, Cristina; Soriano, José; Soler, Joaquim
Highlights: Present-centered awareness was related to depressive symptoms, but not to psychiatric diagnosis Acceptance was related to both depressive symptoms and psychiatric diagnosis Associations between psychopathology, mindfulness and depression vary depending on mindfulness facets Results highlight the importance of increasing acceptance in different clinical populations Abstract: The aim of the present study was to determine 1) whether deficits in two mindfulness dimensions (present-centered awareness and acceptance) were present in individuals with different psychiatric conditions and 2) whether co-existing depressive symptoms affected the mindfulness-related capacities in these groups. A total of 246 individuals, both clinical and non-clinical participants, were included in this study. The clinical sample consisted of 162 individuals; of these, 43 had a diagnosis of cocaine dependence while the remaining 119met clinical criteria for eating disorders (n = 43), major depressive disorder in remission (n = 39), and borderline personality disorder (n = 45). A non-clinical (NC) community sample consisting of 76 individuals was included as a control group. All participants completed self-report instruments to assess present-centered awareness, acceptance, and depressive symptoms. Present-centered awareness scores were significantly associated with depressive symptoms but not with the diagnostic group. By contrast, a significant effect of depressive symptoms and diagnostic group was associated with acceptance scores, with all clinical groups presenting significantly lower scores than the NC sample. These findings suggest that the association between psychopathology, mindfulness, and depressive symptoms varies depending on the specific aspect of mindfulness aspect (i.e., awareness or acceptance) evaluated.